2012
DOI: 10.1210/jc.2011-3441
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Granulosa Cells from Polycystic Ovary Syndrome Patients with and without Insulin Resistance: Identification of Susceptibility Gene Sets through Network Analysis

Abstract: Microarray analysis demonstrated differential expression of genes linked to diabetes mellitus, inflammation, cardiovascular diseases, and infertility in the granulosa cells of PCOS women with and without insulin resistance. Because these dysregulated genes are also involved in oxidative stress, lipid metabolism, and insulin signaling, we hypothesize that these genes may be involved in follicular growth arrest and metabolic disorders associated with the different phenotypes of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 22 publications
6
105
1
Order By: Relevance
“…HOMA-IR was calculated using the following equation: HOMA-IR = FPG (mM) × FINS (mIU/L)/22.5 [20]. Moreover, the follicles in basal 2–9 mm of left and right ovaries were counted using ultrasound.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HOMA-IR was calculated using the following equation: HOMA-IR = FPG (mM) × FINS (mIU/L)/22.5 [20]. Moreover, the follicles in basal 2–9 mm of left and right ovaries were counted using ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…Ovarian stimulation and oocyte retrieval were performed according to a previously described protocol [20]. Human chorionic gonadotropin (hCG) was injected to trigger ovulation after adequate follicular development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCOS compared to non-PCOS (Catteau-Jonard et al 2008, Wei et al 2012, Meng et al 2013, Schmidt et al 2014, Lan et al 2015, endometriosis compared to non-endometriosis , Allegra et al 2014, Barcelos et al 2015 and diminished ovarian reserve compared to normal ovarian reserve (Greenseid et al 2011, Jindal et al 2012, May-Panloup et al 2012) have all been shown to alter gene expression. In fact, PCOS patients with or without insulin resistance were shown to have DRGE compared to non-PCOS normal control patients (Kaur et al 2012). Other pathologies may also alter gene expression but have not been examined.…”
Section: Variables Affecting Granulosa Cell Transcriptomic Profiles Omentioning
confidence: 99%
“…There has been little overlap in the genes differentially expressed across studies and tissues; however, altered expression of Wnt-signaling pathway components was observed in both whole ovary and theca cells (92,93). Comparisons of granulosa cells from PCOS subjects with and without insulin resistance and healthy control samples has shown that insulin-resistant subjects have gene expression profiles enriched for type 2 diabetes genes, whereas non-insulinresistant subjects predominantly up-regulate inflammatory genes (95). Other studies using expression profiling from PCOS and control theca cells to perform in silico analysis of enriched transcription factor-binding sites found that the POU5 class 1 and hepatocyte nuclear factor sites are significantly overrepresented in PCOS theca expression regulation and are likely to play a role in granulosa proliferation and follicular growth and atresia (96).…”
Section: Use Of Functional Data To Identify Causal Loci/genesmentioning
confidence: 99%